AI-Powered Multi-Modal Form Filling: Advancing Accessibility through Voice and Image Recognition - Waseem Syed (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The rapid evolution of artificial intelligence in image and voice recognition has significantly enhanced the accessibility of digital interactions. This article discusses a multi-modal form filling approach that integrates real-time voice transcription and image-based data extraction. This integration not only mitigates the cognitive and physical challenges associated with traditional form-filling but also enriches user engagement and inclusivity. We demonstrate how the application of this technology streamlines data entry processes and notably improves accessibility for diverse user groups, establishing a new benchmark in user-friendly digital interactions. Results from various implementations show enhanced processing efficiency, a reduction in error rates, and high user satisfaction across different sectors, reinforcing the transformative potential of AI in making digital forms more accessible and efficient while adhering to high accuracy and satisfaction standards.